Cyprus - Fox, Mary Virginia (Chicago : Childrens Press, 1993)
Presents the geography, history, and customs of the divided Mediterranean island of Cyprus.
Includes index.
School Library Journal.
Wilson's Children.
Wilson's Junior High School.
6.
8.9
Keywords: Cyprus -- Juvenile literature; Cyprus; Cyprus